An Oral Approach for Teaching English Communicatively at the Ecuador National Police, 101 Metropolitan Assistance Central Station - Llumigusín Criollo, Bairon Iván (2007)
The Metropolitan Assistance Central Station is 69 years old, and from the first year until nowadays has been the channel of communication between the citizen and the National Police. This communication has always been by phone during the first years people who dialed 101 were always Ecuadorian. Once foreign started to call this number to ask for information but they used to speak English and Ecuadorian police officer were not able to neither understand nor communicate in this language. When the foreigners that speak English call Metropolitan Assistance Central Station, they do not have a proper attention, because the staff who work there do not have the appropriate training in the English language. To put an end to this disadvantage, the present project conformed of five chapters is presented: Chapter One presents the antecedents of the Metropolitan Assistance Central Station and their difficulties with the English area. Then it shows the oral skill for using the English language communicatively, concept of language and its communication system, and it concludes dealing with the pronunciation and oral communication. Chapter Two shows shortly the methods of research that are necessaries to apply on the present project to begin by basic concepts and concluding with the procedures for data collection. Chapter Three, there are the graphics where the results of the analysis and interpretation of data compiled are presented. Chapter Four contains the conclusions and recommendations obtained after concluding the research. And finally, Chapter Five shows the proposal "An Oral Approach for Teaching English Communicatively at the Ecuador National Police, 101 Metropolitan Assistance Central Station", where the principal subject is to teach English without having to use four abilities that all English student should have: speaking, listening, reading and writing. In this research, speaking and listening are emphasized because the place where this work will be used, the communication is mainly oral.